Randomized Controlled Trials 2: Analysis - Foley, Robert N; Parfrey, Patrick S (Methods in molecular biology (Clifton, N.J.), 2021)
When analyzing the results of a trial, the primary outcome variable must be kept in clear focus. In the analysis plan, consideration must be given to comparing the characteristics of the subjects, taking account of differences in these characteristics, intention-to-treat analysis, interim analyses and stopping rules, mortality comparisons, composite outcomes, research design including run-in periods, factorial, stratified and crossover designs, number needed to treat, power issues, multivariate modeling, subgroup analysis, competing risks, and hypothesis-generating analyses.